Botanical characterisation of natural honey samples from a high altitudinal region, Gümüşhane, east-Türkiye. Issue 1 (2nd January 2023) - Tosunoglu, Hakan; Tosunoglu, Aycan; Ergün, Nilgün; Bicakci, Adem
Abstract: The aim of our study is to determine important honey resources and botanical characterisation of honey in a high-altitude region of Türkiye. Natural honey samples were collected from all possible locations in 2017. The melissopalynological analysis identified 14 unifloral honey samples, and many plants were also determined as important sources for multifloral honey. Principal component analysis separated honey samples from low-altitude regions while high-altitude regions form a tight cluster. Pollen diversity was found to be lower in honeys at low altitudes and higher pollen diversity was found in honeys at high altitudes. Altitude plays an important role in the pollen content of the honey, with Cornus mas, Asteraceae, and Hypericum being indicator pollen types above 1500 m; Castanea sativa and Myosotis pollen were found predominant or secondary under 1100 m altitude. This has allowed the altitude preferences of some plants, which are important for beekeeping, to be associated with the location of the apiaries and, therefore, the composition of the honey.